Hubungan Aktivitas Belajar dengan Hasil Belajar Siswa dalam Pembelajaran IPS di Kelas V Sekolah Dasar - Suri, Atika; Hamimah, Hamimah; Zuardi, Zuardi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
THE CORRELATION OF STUDENTS’ LEARNING ACTIVITIES AND THEIR LEARNING OUTCOMES OF SOCIAL SCIENCE SUBJECT AT CLASS V OF PRIMARY SCHOOLS AbstractThis research is done due to the fact that student’s learning activities and their learning outcomes of Social Science subject were still low. This research aims at finding out the correlation between the learning activities and learning outcomes of Social Science subject at class V. This quantitative research applied the correlational method. The population was all 5th grade students of SD Semen Padang with the total number of 43 students. Sample were chosen by using saturation sampling technique. The research result show that there is a positive and strong realitionship between students’ activities and their learning outcomes with the correlation coefficient of 0.798.Keywords: Learning Activities, Learning Outcomes